L-cysteine modified silver nanoparticles for selective and sensitive colorimetric detection of vitamin B1 in food and water samples - Beeta Rani Khalkho; Ramsingh Kurrey; Manas Kanti Deb; Kamlesh Shrivas; Santosh Singh Thakur; Shamsh Pervez; Vikas Kumar Jain (Heliyon, 2020)
The use of L-cysteine modified silver nanoparticles (Cys-capped AgNPs) as a colorimetric probe for determination of vitamin B1 (thiamine) is described in the present work. This method is based on the measurement of red shift of localized surface plasmon resonance (LSPR) band of Cys-capped AgNPs in the region of 200–800 nm. The color of Cys-capped AgNPs was changed from yellow to colorless by the addition of vitamin B1. The mechanism for detection of vitamin B1 is based on the electrostatic interaction between positively charged vitamin B1, which causes the red shift of LSPR band from 390 nm to 580 nm. The interaction between Cys-capped AgNPs and vitamin B1 was theoretically explored by density function theory (DFT) using LANL2DZ basis sets with help of Gaussian 09 (C.01) program. The morphology, size distribution and optical properties of Cys-capped AgNPs were characterized by transmission electron microscope (TEM), UV-Visible spectrophotometry, Fourier transform infrared spectroscopy (FTIR) and dynamic light scattering (DLS) techniques. The method is linear in the range of 25–500 μg mL−1 with correlation coefficient (R2) 0.992 and limit of detection of 7.0 μg mL−1. The advantages of using Cys-capped AgNPs as a chemical sensor in colorimetry assay are being simple, low cost and selective for detection of vitamin B1 from food (peas, grapes and tomato) and environmental (river, sewage and pond) water samples.